Global role for coactivator complexes in RNA polymerase II transcription. Issue 1 (1st January 2019) - Fischer, Veronique; Schumacher, Kenny; Tora, Laszlo; Devys, Didier
ABSTRACT: SAGA and TFIID are related transcription complexes, which were proposed to alternatively deliver TBP at different promoter classes. Recent genome-wide studies in yeast revealed that both complexes are required for the transcription of a vast majority of genes by RNA polymerase II raising new questions about the role of coactivators.